A comparative propensity score‐matched analysis of perioperative outcomes of intracorporeal vs extracorporeal urinary diversion after robot‐assisted radical cystectomy: results from the International Robotic Cystectomy Consortium. (16th May 2020) - Hussein, Ahmed A.; Elsayed, Ahmed S.; Aldhaam, Naif A.; Jing, Zhe; Peabody, James O.; Wijburg, Carl J.; Wagner, Andrew; Canda, Abdullah Erdem; Khan, Mohammad Shamim; Scherr, Douglas; Schanne, Francis; Maatman, Thomas J.; et al.
Abstract : Objective: To compare the perioperative outcomes of intracorporeal (ICUD) vs extracorporeal urinary diversion (ECUD) after robot‐assisted radical cystectomy (RARC). Patients and Methods: We retrospectively reviewed the prospectively maintained International Robotic Cystectomy Consortium (IRCC) database. A total of 972 patients from 28 institutions who underwent RARC were included. Propensity score matching was used to match patients based on age, gender, body mass index (BMI), American Society of Anesthesiologists Score (ASA) score, Charlson Comorbidity Index (CCI) score, prior radiation and abdominal surgery, receipt of neoadjuvant chemotherapy, and clinical staging. Matched cohorts were compared. Multivariate stepwise logistic and linear regression models were fit to evaluate variables associated with receiving ICUD, operating time, 90‐day high‐grade complications (Clavien–Dindo Classification Grade ≥III), and 90‐day readmissions after RARC. Results: Utilisation of ICUD increased from 0% in 2005 to 95% in 2018. The ICUD patients had more overall complications (66% vs 58%, P  = 0.01) and readmissions (27% vs 17%, P  = 0.01), but not high‐grade complications (21% vs 24%, P  = 0.22). A more recent RC era and ileal conduit diversion were associated with receiving an ICUD. Higher BMI, ASA score ≥3, and receiving a neobladder were associated with longer operating times. Shorter operating time was associated with male gender, older age, ICUD, and centres with a larger annual average RC volume. Longer intensive care unit stay was associated with 90‐day high‐grade complications. Higher CCI score, prior radiation therapy, neoadjuvant chemotherapy, and ICUD were associated with a higher risk of 90‐day readmissions. Conclusions: Utilisation of ICUD has increased over the past decade. ICUD was associated with more overall complications and readmissions compared to ECUD, but not high‐grade complications.